Strategi Meningkatkan Penjualan melalui Digital Marketing dan Branding Produk UMKM di Desa Gadog Cianjur Jawa Barat - Lestari, Rahayu; Hardini, Resti; Waluyo, Tri; Elwisam, Elwisam (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Report is written with a point to prove the influence of the cost of education, as well as the location of the decision of parents educate their children through groups reference in Tangerang and South Jakarta. The purpose of this study is to conduct an analysis related to efforts to increase sales through digital marketing and branding of MSME products in Gadog Village – Cianjur, West Java. Sampling based on Purposeive Sampling technique, as many as 45 respondents using proportional random sampling. The analysis method used statistically-partial least sguare using the SMART PLS 4 software analysis tool.The results showed that digital marketing has a positive and significant effect on sales levels, branding has a positive but not significant effect on sales levels